MUSLIM FEMALE CONTENT CREATOR ON TIKTOK @HELWABASWEL AS AN INSPIRATION FOR OOTD TRENDS FOR STUDENTS - Nurfatin Safika; Mailin Mailin (Program Pascasarjana UIN Sumatera Utara, 2025)
This study examines the phenomenon of Muslimah content creators on TikTok, particularly the @helwabaswel account, as a source of Outfit of the Day (OOTD) inspiration for students of the Islamic Communication and Broadcasting (KPI) Study Program, Faculty of Da'wah and Communication (FDK), UIN Sumatera Utara. The research aims to describe the characteristics of the OOTD content presented, analyze KPI students' responses to the content, and assess its influence on their clothing styles. Using a qualitative phenomenological approach, data were collected through in-depth interviews, participatory observation, and documentation. The findings reveal that @helwabaswel's OOTD content showcases modest fashion that aligns with Islamic principles, combining visual aesthetics, soft color trends, and subtly embedded da'wah messages. KPI students responded positively, using the content as a guide to dress stylishly yet modestly, while also motivating themselves to increase awareness of Islamic dressing. However, some informants remained critical of the commercial elements present in the content. These findings highlight that Muslimah content creators on TikTok serve not only as fashion icons but also as cultural da'wah agents, influencing the construction of identity and dress practices among young Muslim women in the university environment.